Fermentação de mosto com alto teor de sacarose para a produção de bioetanol combustível por diferentes linhagens de Saccharomyces cerevisiae usando alta densidade celular - Barbosa, Heloisy Suzes [UNESP] (2013)
The production of fuel ethanol in Brazil is currently obtained by fermentation of sugar cane juices and/or molasses which have around 20% of dissolved solids leading the alcoholic yield to be smaller than that desired. Thus, large volumes of vinasse are generated, leading to high energy consumption in distillation. Taking into account the renewed interest in improving the process to obtain higher levels of ethanol, and reduce expenses associated with the process, new studies are being conducted to determine the adequacy of industrial strains of Saccharomyces cerevisiae in the fermentation of concentrated media with fermentable sugars. In this context the present work aims to study the fermentation characteristics of five industrial strains, four used in Brazilian industries PE-2, CAT-1, SA-1 and BG, and a Ethanol REDTM, used in corn bioethanol production. The fermentation process was carried out in simple batch at 30° and 37°C with 250 rpm rotation. The sucrose concentration in the fermentation medium varied between 21 and 30% (w/v) focusing on Very High Gravity Fermentation Technology conditions - musts with high levels of fermentable sugars, with or without supplementation with peptone and yeast extract at pH 5.0; and with high cell density. The fermentation profile was assessed by determining parameters such as biomass, cell viability, consumption of carbon source, ethanol and production of used for trehalose. Wine with ethanol content ranging between 17 to 20% (v/v) was obtained at the end of the fermentation musts which had sucrose 30 to 35% (w/v). Supplementation with nitrogen source led to an improvement in the performance of industrial yeasts fermentation. High levels of trehalose were observed during the fermentation process as compared to the cells in stationary phase used as inoculum, as well as growing cells, suggesting that industrial strains have the ability to adapt to the stressing conditions of caused by high gravity...